Islamic Parenting Dalam Mendidik Anak Di Era Modern Menurut Perspektif Islam - Maghfiroh, Canggih Nailil (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The foundation of a children's personality will be built perfectly because of the education they received in childhood. Parents carry out an educational role with positive and effective patterns of action or parenting. Family involvement in a child's education is a must. The form of education in the family is nurturing. Parenting is closely related to parents' ability to provide attention, time and support to meet physical, mental, social, emotional and spiritual needs. The environment greatly influences children's development, especially in the family, because the family is the beginning of education and the formation of people in society who are responsible for the continuity of generations. The aim of religious activities in Educating Children in the Modern Era from an Islamic Perspective is to form good character or morals by instilling moral values, behavior and speech in children in the modern era and to improve the quality of parents in terms of education. children in the modern era from an Islamic perspective. The method used in this community service activity is a sociological and psychological approach. This activity was carried out in Garurejo hamlet, Gongseng village, Megaluh sub-district, Jombang district. This activity was attended by 66 Yasin Tahlil congregations and religious and community leaders in Garurejo hamlet. This target is determined based on the needs and objectives of Islamic Parenting activities, namely the mothers of the Yasin Tahlil congregation in Garurejo hamlet. The results of this activity are that with this program it is hoped that parents will understand more about the knowledge of educating children in the modern era. Parents and children can apply the material explained by the presenter in their daily lives.